Expression of glutamine synthetase in the mouse kidney: localization in multiple epithelial cell types and differential regulation by hypokalemia - Verlander, Jill W. (American Physiological Society, 2013)
Renal glutamine synthetase catalyzes the reaction of NH(4)(+) with glutamate, forming glutamine and decreasing the ammonia available for net acid excretion. The purpose of the present study was to determine glutamine synthetase's specific cellular expression in the mouse kidney and its regulation by hypokalemia, a common cause of altered renal ammonia metabolism. Glutamine synthetase mRNA and protein were present in the renal cortex and in both the outer and inner stripes of the outer medulla. Immunohistochemistry showed glutamine synthetase expression throughout the entire proximal tubule and in nonproximal tubule cells. Double immunolabel with cell-specific markers demonstrated glutamine synthetase expression in type A intercalated cells, non-A, non-B intercalated cells, and distal convoluted tubule cells, but not in principal cells, type B intercalated cells, or connecting segment cells. Hypokalemia induced by feeding a nominally K(+)-free diet for 12 days decreased glutamine synthetase expression throughout the entire proximal tubule and in the distal convoluted tubule and simultaneously increased glutamine synthetase expression in type A intercalated cells in both the cortical and outer medullary collecting duct. We conclude that glutamine synthetase is widely and specifically expressed in renal epithelial cells and that the regulation of expression differs in specific cell populations. Glutamine synthetase is likely to mediate an important role in renal ammonia metabolism.